Mass spectrometry as a preparative tool for the surface science of large molecules - Rauschenbach, S; Ternes, M; Harnau, L; Kern, K (Annual Reviews, 2016)
Measuring and understanding the complexity that arises when nanostructures interact with their environment are one of the major current challenges of nanoscale science and technology. High-resolution microscopy methods such as scanning probe microscopy have the capacity to investigate nanoscale systems with ultimate precision, for which, however, atomic scale precise preparation methods of surface science are a necessity. Preparative mass spectrometry (pMS), defined as the controlled deposition of m/z filtered ion beams, with soft ionization sources links the world of large, biological molecules and surface science, enabling atomic scale chemical control of molecular deposition in ultrahigh vacuum (UHV). Here we explore the application of high-resolution scanning probe microscopy and spectroscopy to the characterization of structure and properties of large molecules. We introduce the fundamental principles of the combined experiments electrospray ion beam deposition and scanning tunneling microscopy. Examples for the deposition and investigation of single particles, for layer and film growth, and for the investigation of electronic properties of individual nonvolatile molecules show that state-of-the-art pMS technology provides a platform analog to thermal evaporation in conventional molecular beam epitaxy. Additionally, it offers additional, unique features due to the use of charged polyatomic particles. This new field is an enormous sandbox for novel molecular materials research and demands the development of advanced molecular ion beam technology.